KIWAKKUKI - Women fight against HIV/AIDS. An encouraging example for social work in Tanzania - Iris Strauch (Social Work and Society)
For 20 years, AIDS has continued its relentless spread across the globe. By the end of the year 2000, the United Nations' Joint Programme on HIV/AIDS reported that 36.1 million men, women, and children around the world were living with HIV and 21.8 million had died of it. Though AIDS is now found in every country, it has most seriously affected sub-Saharan Africa - home to 70 % of all adults and 80 % of all children living with HIV, and the continent with the least medical resources in the world. Today, AIDS is the primary cause of death in Africa and it has had a devastating impact on villages, communities and families. In many African countries, the number of newly infected persons is increasing at a rate that is threatening to destroy the social fabric. Life expectancy is decreasing rapidly in many of these countries as a result of AIDS related illnesses and socioeconomic problems. Of the approximately 13.2 million children orphaned by HIV/AIDS worldwide, 12.1 million live in Africa.